Comparative investigation of different blends ageing behaviours for short-term thermal oxidation ageing mechanism of SBS-modified bitumen. Issue 4 (3rd April 2023) - Zhang, Henglong; Yang, Xue; Lin, Yunteng; Wu, Chaofan; Jiang, Xing; Chen, Zihao
Abstract : Instead of styrene-butadiene-styrene triblock copolymer (SBS) modified bitumen (SBSMB) being taken as a whole to be investigated in most of previous aging mechanism studies, the respective contributions of SBS and bitumen matrix to SBSMB aging behavior were evaluated in this research. Four bituminous samples including the blend of aged SBS with fresh bitumen matrix (TAS+B), the blend of un-aged SBS with aged bitumen matrix (S+TAB), un-aged and short-term aged SBSMB, were prepared and then compared in terms of physical and rheological properties, molecular size and morphological polymer phase structure. The results indicate the thermal degradation of copolymer and the aging hardening of bitumen matrix jointly determine the SBSMB aging behaviors. The bitumen matrix aging effect outweighs the copolymer aging effect in view of ductility, viscosity and complex modulus results, and the quantitative relationship formulated between these two effects is valid in some cases.